STRATEGI PENINGKATAN MOTIVASI KERJA PEKERJA HARIAN LEPAS (DAILY WORKER) BERBASIS ANALISIS SWOT DI KOTA BANDUNG - Satria Putra Prasetia; Recky Recky; Ida Farida Oesman; Nazarudin Nazarudin (Komunitas Manajemen Kompetitif, 2026)
This study aims to formulate a strategy to improve the work motivation of daily workers in Bandung City through an integration of a phenomenological approach and a SWOT analysis. Despite their significant contribution to the urban economy, this group often faces income uncertainty, minimal social security, and weak bargaining power, which directly affect the stability of work motivation. This gap is exacerbated by the dominance of previous studies that are linear quantitative or macro-juridical, leaving a gap in mapping motivation strategies that are based on subjective experiences and operationally measurable. This study uses a convergent mixed design, with a sample of 10 respondents selected through purposive and snowball sampling techniques until data saturation is reached. Data collection was carried out through a five-point Likert scale questionnaire (20 items) and contextual observation. Data were analyzed in stages: factor weighting using the IFAS-EFAS matrix, cross-strategy formulation using the TOWS matrix, and interpretive triangulation with phenomenological narratives. The research findings are expected to provide theoretical contributions in the form of an adaptive work motivation analysis model for flexible workers, while also generating applicable strategic recommendations for local governments and businesses in designing inclusive, measurable, and field-relevant HR interventions.